ELABORAÇÃO DE UM INSTRUMENTO COM AS ETAPAS DO PROCESSO DE ENFERMAGEM PARA UMA MATERNIDADE DE RISCO HABITUAL - Maurer, Fabiele Rodrigues (2019)
Introduction: The neonatal and maternal health care in current context presents as a priority subject matter in health care scope, because there is a big concern in promoting paradigm changes in the current obstetric model. In order for this care to actualize in the construct of nurses’ action there are various modalities of care used in nursing practice. Among them the Nursing Assistance Systematization which was regulated in Brazil as a method that organizes the professional work making possible the implantation of Nursing Process that configures was a methodological tool which guides the care and the professional practice. General Objective: To elaborate a tool with stages of Nursing Process to a low risk maternity. Specifics Objectives: Produce a model of nursing history tool to a low risk maternity; Delineate clinics and obstetrics data of pregnant women, parturient and puerperal woman attended in a low risk maternity; Identify the nursing diagnosis most prevalent in a low risk maternity framing a care plan to each listed diagnosis; Qualify the nurses about the utilization of a tool with the nursing process stages in a low risk maternity; Evaluate the application and contribution of the professional qualification to use a tool with the nursing process stages to a low risk maternity. Methods: A research-action study made by focal group technique realized with nurses from a low risk maternity in south of Brazil. Results: Among the results there is the experience report about the production of a nursing history tool model to a low risk maternity, based in the theory of basic human needs. The construction of a nursing history for a low risk maternity consolidates the current legislation. Furthermore, the inserted stages in the tool lined with the theory of basic humans needs enable a comprehensive and effective care to parturients. Beyond that there is in the results the identification of most prevalent nursing diagnosis in a low risk maternity relating with their definer characteristics and related factors. The most prevalent diagnosis were ineffective infant feeding pattern, interrupted breastfeeding, disposition for improved breastfeeding, ineffective breast milk production, impaired gas exchange and disturbed sleep pattern/ sleep deprivation. Based in these evidences was possible to interrelate and create interactive discussions in the labour and delivery nurses group contributing to rethinking the work process and making feasible the importance of nursing assistance systematization. Final considerations: This study provided the development of a tool with the nursing process stages in an interactive and interrelated way by the focal meetings. The meetings enabled the awareness of the labour and delivery nurses and aroused their theoretical and methodological interest about the Nursing Assistance Systematization. Created product: The final product was developed from a tool with the Nursing Process to a low risk maternity. The tool is presented with socio demographics and clinical data for parturient and the other stages are related with the nursing historic, most prevalent nursing diagnosis found in the research process, Nursing Planning, Nursing Implementation and Evaluation. All the stages of this tool were substantiated in the Wanda de Aguiar Horta’s Basic Humans Needs Theory, which enable to guide the care management to a low risk maternity subsidizing a future informatization of this created tool.